2019
DOI: 10.1021/acschemneuro.9b00225
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Activates Toll-Like Receptor 4 to Induce Central Immune Signaling within the Ventral Tegmental Area and Contributes to Extracellular Dopamine Increase in the Nucleus Accumbens Shell

Abstract: Methamphetamine (METH) is a globally abused, highly addictive stimulant. While investigations of the rewarding and motivational effects of METH have focused on neuronal actions, increasing evidence suggests that METH can also target microglia, the innate immune cells of the central nervous system, causing release of proinflammatory mediators and therefore amplifying the reward changes in the neuronal activity induced by METH. However, how METH induces neuroinflammatory responses within the central nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 59 publications
0
56
0
Order By: Relevance
“…Indeed, a recent report examining METH's effects on TLR4 signaling and VTA-NAc dopamine transmission provides convincing evidence of this fact. In this study, Wang X. et al (2019) report that METH can bind to lymphocyte antigen 96 (i.e., MD-2), which interacts directly with TLR4 to confer receptor responsiveness to LPS, and that inhibition of TLR4 attenuated METH-induced NF-κB activation in microglia. In addition, this study also showed that METH upregulates IL-6 within the VTA and that this is associated with enhanced extracellular dopamine within the NAc, and treatment with the TLR4 inhibitor (+) naloxone or an intra-VTA IL-6 antibody reduces METH-induced increases in NAc dopamine (Wang X. et al, 2019).…”
Section: Methamphetaminementioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, a recent report examining METH's effects on TLR4 signaling and VTA-NAc dopamine transmission provides convincing evidence of this fact. In this study, Wang X. et al (2019) report that METH can bind to lymphocyte antigen 96 (i.e., MD-2), which interacts directly with TLR4 to confer receptor responsiveness to LPS, and that inhibition of TLR4 attenuated METH-induced NF-κB activation in microglia. In addition, this study also showed that METH upregulates IL-6 within the VTA and that this is associated with enhanced extracellular dopamine within the NAc, and treatment with the TLR4 inhibitor (+) naloxone or an intra-VTA IL-6 antibody reduces METH-induced increases in NAc dopamine (Wang X. et al, 2019).…”
Section: Methamphetaminementioning
confidence: 85%
“…In this study, Wang X. et al (2019) report that METH can bind to lymphocyte antigen 96 (i.e., MD-2), which interacts directly with TLR4 to confer receptor responsiveness to LPS, and that inhibition of TLR4 attenuated METH-induced NF-κB activation in microglia. In addition, this study also showed that METH upregulates IL-6 within the VTA and that this is associated with enhanced extracellular dopamine within the NAc, and treatment with the TLR4 inhibitor (+) naloxone or an intra-VTA IL-6 antibody reduces METH-induced increases in NAc dopamine (Wang X. et al, 2019). This study parallels findings described above by Brown et al (2018), which demonstrated reduced cocaine-primed reinstatement following intra-VTA treatment with a TLR4 antagonist.…”
Section: Methamphetaminementioning
confidence: 85%
“…administration of only one dose, five days before splenocyte culture [ 66 ]. These data suggest that similar pathways may be triggered by amphetamine and Con A in immune cells, which could be explained by recent evidence that methamphetamine is a TLR4 agonist (see below) [ 168 ]. As far as we know, the simultaneous enkephalinergic activation in immunocytes and in the brain following exposure to amphetamine is the only evidence of a drug of abuse inducing similar biological changes in both systems.…”
Section: How Psychostimulants Can Influence Peripheral Immunitymentioning
confidence: 59%
“…This observation complements the observation of Zhang and colleagues who showed a meth‐induced increase in NF‐κB activation in cultured astrocytic cells (Zhang et al., 2015). Meth increases TNF‐α receptor expression (Park et al., 2017) and activates TLR4 (Wang et al., 2019). These actions of meth may underlie the increased NF‐κB activation observed in the non‐Tg rats.…”
Section: Discussionmentioning
confidence: 99%